Morphological description of two scallops, Chlamys albida (Arnold, 1906) and Volachlamys tranquebaria (Gmelin, 1791) from the coastal waters of the northern Bay of Bengal - MD ROYHANUR ISLAM; M. SHAHADAT HOSSAIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Islam MDR, Hossain MS. 2024. Morphological description of two scallops, Chlamys albida (Arnold, 1906) and Volachlamys tranquebaria (Gmelin, 1791) from the coastal waters of the northern Bay of Bengal. Biodiverstas 25: 900-907. The commercial marine scallop Chlamys albida (Arnold, 1906) was first discovered in the Sonadia, Bangladesh coastal island. It was acquired and deposited in the Institute of Marine Sciences (IMS) museum catalog, University of Chittagong. The species was taxonomically studied based on its external morphology as well as compared with Volachlamys tranquebaria (Gmelin, 1791), a species from the same family of Pectinidae, which was previously reported along the coast of Bangladesh. Study specimens were collected randomly and hand-picked from the intertidal zone of Sonadia Island. This study examined morphological characteristics as well as morphometric measurements. The study also determined the studied species distribution pattern, habitat biology, and ecology. This species has not yet been registered in this region, presumably due to the lack of long-term research on bivalves and its low abundance. The present study increased the number of reported mollusc species in Bangladesh, which may facilitate further molluscan research.